2020
DOI: 10.1111/psyg.12644
|View full text |Cite|
|
Sign up to set email alerts
|

Depression among older adults: a systematic review ofSouth Asian countries

Abstract: The world's population has been evolving rapidly; every country in the world is facing this drastic progression in the number and the percentage of the elderly in their net population. As the chronological age advances, physiological and psychosocial decline will be evident among all older adults. The potentially relevant literature was identified using appropriate search terms in electronic databases such as PubMed MEDLINE, Scopus, ProQuest, Web of Science, CINAHL, IndMed, and Google Scholar. Articles publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 96 publications
(188 reference statements)
2
18
1
3
Order By: Relevance
“…Among the socio-demographic factors, the female gender is the most frequently associated with depression and anxiety [21,23,[27][28][29][30][31]. These findings are consistent with other reviews focused on the general population and healthcare workers during the pandemic [6,7] and more studies before COVID-19 [19,34,35]. Previous research suggests that this gender disparity may be mediated by variables that concern work, economic, educational, neuro-hormonal, psychological and genetic aspects [34,[36][37][38].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Among the socio-demographic factors, the female gender is the most frequently associated with depression and anxiety [21,23,[27][28][29][30][31]. These findings are consistent with other reviews focused on the general population and healthcare workers during the pandemic [6,7] and more studies before COVID-19 [19,34,35]. Previous research suggests that this gender disparity may be mediated by variables that concern work, economic, educational, neuro-hormonal, psychological and genetic aspects [34,[36][37][38].…”
Section: Discussionsupporting
confidence: 86%
“…Physical and mental health have been previously associated with depression and anxiety [6,35,37]. In our review, the results regarding the factors related to physical health show some variability depending on the outcome.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In this nationally representative study, with middle-aged and elderly community-resident participants, we found that the prevalence of depression in middle-aged and older people was 19.4%, which was lower than the prevalence reported in the previous study (35.2%) [ 44 ] and lower than those in India (41%) and South Asian countries (42%) [ 45 ]. However, it was higher than the world’s median of depression in an older population of 10.3% (interquartile range [IQR], 4.7–16.0%) [ 4 ], which in turn was higher than the 13% rate in the United States [ 46 ], 13.9% in Sri Lanka [ 13 ] and 18.5% in Thailand [ 47 ].…”
Section: Discussioncontrasting
confidence: 62%
“…Depression is the most common mental health disorder in the elderly population and is associated with functional, cognitive, physical, and social impairments [2]. A recent meta-analysis of 120 studies, which were conducted in South Asian countries, revealed that the overall pooled prevalence of depression among the elderly was 42.0% [3]. A previous meta-analysis of 25 studies from Western countries (Europe and North America) found a prevalence of depressive symptoms among older adults living in the community at 19.5% [4].…”
Section: Introductionmentioning
confidence: 99%